Предмет: Алгебра,
автор: Milena94
1)корень из (х-1) умноженное на корень из (х+4) и равно 6 2) х + корень из (х^2-9) = 21 3) корень из (х+3) = 9-х 4) 5 корень из (х-2) = х+2
Ответы
Автор ответа:
0
1){x-1>0, x+4>0 x>1 } (х-1)(х+4)=36 х^2+3x-40=0 x1,2=(-3+-корень(9+169))2= (-3+-13)2 х=5, второй корень не входит в область определения.
2){х^2-9>0 x>3 x<-3} x^2-9=(21-x)^2 x^2-9= 441-42x+x^2 42x=450 x=757=
=10 57
3){x>-3} x+3=81-18x+x^2 x^2-19x+79=0 x1,2=(19+-корень (361-316))2=
=(19+-3корень5)2
4){х>2} 25x-50=x^2+4X+4 x^2-21x+54=0 x1,2=(21+-корень(441-216) )2=
(21+-15)2 x1=18 x2=3
Похожие вопросы
Предмет: Алгебра,
автор: Alexa189
Предмет: Биология,
автор: Аноним
Предмет: Русский язык,
автор: Renattooo
Предмет: Физика,
автор: bun
Предмет: Химия,
автор: dmitroR